The Role of Krishi Vigyan Kendras (KVK) in Strengthening National Agricultural Research Extension System in India - Sahoo, Alok K.; Sahu, Susrita; Meher, Sanat K.; Begum, Rukeiya; Panda, Tarak C.; Barik, N. C. (Insights into Economics and Management Vol. 8, 2021)
Agricultural development of any country depends upon its research and development along with extension agencies creating a network of Research-Extension system which also known as Agricultural Knowledge Information System (AKIS). AKIS is described as knowledge triangle formed by research, education, extension and farmers at heart of the triangle. To strengthen National Agricultural Research Extension System (NARES), ICAR has initiated several frontline extension approaches such as National Demonstration (1964), Operational Research Project (1974), Krishi Vigyan Kendra (1974), and Lab to Land program (1979) which clubbed together in KVK in 1992. The mandate of KVK has been evolved from vocational training to Technology Assessment and Demonstration for its Application and Capacity Development in a district for its rising contribution in NARES in India. Though technologies generation at Research centre of ICAR or State Agricultural University, but technology assessment for location specificity, refinement for micro location on farm real problem basis, then final validation of technologies for large scale adoption by farmers were conducted by KVK. The Technologies Assessment and Refinement (TAR) process validate technologies through on farm trial with active participation of farmers conducting holistic on farm situation analysis by scientists of KVK. The compatible consistent technologies to farmers after TAR were further fed in to extension system for large scale adoption conducting Front Line Demonstration by close supervision of KVK scientist with extension officials for convincing the result. Capacity development of farmers, farm women, rural youth, NGOs, extension functionaries is carried out by KVK through training program, linkage with allied agencies for complementary service provider. KVK also act as Single Window Delivery System and Knowledge Resource Centre for varied technological products supply and advisories to reach larger clients in district through ICT medium. A lot of convergence activities carried out by KVK with stakeholders in a district to provide best service to the farming community in a district.